Perjalanan Menuju Lingkungan Bebas Asap: Peran Indonesia dalam ASEAN Agreement on Transboundary Haze Pollution [The Road to a Haze-Free Environment: Indonesia's Role in ASEAN Agreement on Transboundary Haze Pollution] - Yandri, Aisha Nafitra Putri; Hutapea, Rachel Bianca Theresia; Timothy, Timothy; Sugiyama, Yumi Jocelyn (Verity: Jurnal Ilmiah Hubungan Internasional (International Relations Journal), 2023)
This paper examines Indonesia's participation dynamics since ratifying the ASEAN Agreement on Transboundary Haze Pollution (AATHP) and its contributions to environmental diplomacy. It delineates two main areas: bureaucratic/technical diplomacy and political leadership diplomacy. At the bureaucratic level, Indonesia has engaged significantly in international forums, notably by elevating the haze pollution issue in the ASEAN Ministerial Meetings on Environment and collaborating with Singapore on technological solutions. However, at the political leadership level, Indonesia's focus on international performance, as evidenced by the new Capital city Nusantara project, has hindered the effective implementation of AATHP principles domestically. Recommendations for AATHP and Indonesia's future contributions include expanding the role of Non-Governmental Interests (NGIs) to enhance treaty legitimacy, balancing scientific and political enforcement, and promoting media involvement for public awareness and scrutiny. By adopting these recommendations, Indonesia and ASEAN nations can effectively mitigate transboundary haze pollution in Southeast Asia.